2017
DOI: 10.1016/j.metabol.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The novel exercise-induced hormone irisin protects against neuronal injury via activation of the Akt and ERK1/2 signaling pathways and contributes to the neuroprotection of physical exercise in cerebral ischemia

Abstract: Irisin reduces ischemia-induced neuronal injury via activation of the Akt and ERK1/2 signaling pathways and contributes to the neuroprotective effect of physical exercise against cerebral ischemia, suggesting that irisin may be a factor linking metabolism and cardio-cerebrovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
218
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(229 citation statements)
references
References 59 publications
7
218
2
2
Order By: Relevance
“…The exact mechanisms behind how irisin acts to increase bone formation and decrease resorption remain not fully understood although our data along with others indicate irisin modulating the RANKL-OPG pathway (29). Recently, several investigators have identified roles for irisin as a potential mediator of inflammatory processes in the lung, atherosclerotic lesions, and macrophages (25)(26)(27)61). These include lowered infiltration of immune cells to inflammatory legions, reduced inflammatory adhesion markers [intracellular cell adhesion marker 1 (ICAM1), VCAM1], reduced expression of proinflammatory cytokines (TNF-a, IL-6, CCL2), and suppressed NF-kB activation (27,(62)(63)(64).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The exact mechanisms behind how irisin acts to increase bone formation and decrease resorption remain not fully understood although our data along with others indicate irisin modulating the RANKL-OPG pathway (29). Recently, several investigators have identified roles for irisin as a potential mediator of inflammatory processes in the lung, atherosclerotic lesions, and macrophages (25)(26)(27)61). These include lowered infiltration of immune cells to inflammatory legions, reduced inflammatory adhesion markers [intracellular cell adhesion marker 1 (ICAM1), VCAM1], reduced expression of proinflammatory cytokines (TNF-a, IL-6, CCL2), and suppressed NF-kB activation (27,(62)(63)(64).…”
Section: Discussionmentioning
confidence: 66%
“…Down-regulation of TNF-a may restore the lymphatic architecture, a response we observed with irisin treatment after the onset of TNBS. Irisin has been shown to suppress production of T h 1 cytokines including TNF-a (25,26). Although not tested here, we speculate irisin has direct effects on lymphatic vessels, potentially driving the amelioration of gut inflammatory processes as well as distant inflammatory processes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…I.v. injection of recombinant irisin reduced brain infarct and edema volume and improved the neurological score in MCAO stroke model (Li et al 2017). Systemic irisin administration has also been shown to ameliorate depressive-like behavior in a chronic unpredictable stress model in rats (Wang and Pan 2016).…”
Section: Fndc5/irisin: Other Effects In the Cnsmentioning
confidence: 97%
“…The MCAO model was prepared exactly as described by us previously Li et al, 2017). Briefly, the mice were anaesthetized with 4% choral hydrate (350 mg·kg À1 , i.p.…”
Section: Mouse Mcao Modelmentioning
confidence: 99%